Nutritional status and factors associated with non-institutionalized people over 75 years of age - María Pilar Molés Julio; Aurora Esteve Clavero; María Loreto Maciá Soler (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to determine the factors related to the risk of malnutrition in a non-institutionalized population over 75 years of age. Method: a cross-sectional study was conducted using a questionnaire in a sample of 326 individuals over 75 years of age in Castellón (Spain), during 2015, and selected through intentional sampling. Results: Malnutrition prevalence was 2.8%. 26.9% of the individuals were at risk of malnutrition, whereas women presented a higher rate (31.5%). Women with a good overall health status showed a lower rate than men, 55% and 69%, respectively. Individuals that showed a lower risk of malnutrition are those with a positive perception than those who have a good overall health. Frail elderly people showed a higher risk of malnutrition (57.5%) compared to non-frail subjects (20.2%) p< 0.001. Conclusion: Frail women, self-assessed health, overall health, and use of health care services (nursing consultation) were related to a higher risk of malnutrition.